Synthesis and Antitubercular Activity of N3,N5-Diaryl-4-(5-arylisoxazol-3-yl)-1,4-dihydropyridine- (Journal of Sciences, Islamic Republic of Iran)
5-Arylisoxazolyl-3-carboxaldehydes were condensed with N-aryl acetoaceta¬mide and ammonium acetate in methanol to give N3,N5-diaryl-4-(5-arylisoxazol-3-yl)-1,4-dihydropyridine-3,5-dicarboxamides. All compounds were screened for their antitubercular activity against Mycobacterium tuberculosis (H37Rv). The results for new synthesized compounds showed a moderate activity in comparison to rifampicin.